Sociodemographic and Clinical Characteristics of Adolescents who Attempted Suicide and Differences in Clinical Characteristics Related to Tobacco, Alcohol, and Substance Use - Buket Canlan Özaydın; Mustafa Selahattin Yeşil; Börte Gürbüz Özgür; Hatice Aksu (Addicta: The Turkish Journal on Addictions)
To assess the sociodemographic and clinical characteristics of adolescents who attempted suicide and the clinical differences in terms of different variables between cases with and without tobacco, alcohol, and substance use groups. The medical records of 237 adolescents referred from the pediatric emergency depart- ment to the child and adolescent psychiatry clinic for suicide attempts over the last 5 years were retrospec- tively reviewed. Clinical variables of adolescents with and without tobacco, alcohol, and substance use were compared. Of the participants, 82.7% were female, 29.1% were not attending formal education, and 32.5% had a history of tobacco, alcohol, and substance use. The most common suicide method was drug ingestion (87.3%), primarily psychiatric medication (42.8%). Impulsive attempts accounted for 55.3%. Family prob- lems were the most common stressor (72.6%). Conduct disorder was the most common psychiatric diagnosis. In the tobacco, alcohol, and substance user group, being male (p < .01), having a father who smokes (p = .05) or consumes alcohol (p < .01), having self-injurious behavior (p < .001), having a history of recurrent suicide attempts (p < .05), having a psychiatric diagnosis (p < .001), and not being in the formal education system (p = .01) were more common than in non-tobacco, alcohol, and substance users. Tobacco, alcohol, and substance use in the family, a history of self-injurious behavior, and being outside the educational sys- tem increase suicide risk in vulnerable adolescents. This highlights the need for preventive interventions and psychoeducation to enhance problem-solving skills in response to stressors, given the impulsive nature of most suicide attempts. In addition, since the clinical characteristics of adolescents who admit to the emer- gency department with a suicide attempt are different from those with tobacco, alcohol, and substance use, treatments for the use of tobacco, alcohol, and substance should be planned during treatment and follow-up.